Actions and perceived impact of African swine fever control measures along the smallholder pig value chain in Uganda - Aliro, T.; Odongo, W.; Ståhl, K.; Dione, Michel M.; Okello, D.M.; Masembe, C.; Chenais, E. (Springer, 2023)
Pig production in Uganda is constrained by African swine fever (ASF) which is endemic in the country. Current measures taken by the Government of Uganda in controlling ASF outbreaks include trade and livestock movement restrictions, called “quarantine.” Little is known about the actions of, and impact of value chain actors in response to ASF quarantines. This study describes actions that different stakeholders in the smallholder pig value chain took, and the perceived economic impact, during ASF quarantines. Data was collected in ten focus group discussions (FGD) using participatory epidemiology tools and two key informants’ (KIs) interviews with District Veterinary Officers (DVOs) of Kisoro and Moyo districts in Uganda. The results show that during ASF quarantine, pig value chain actors shifted their activities from formal places such as livestock markets, slaughter slabs, pork butcheries and pork joints to informal places such as farmers’ homesteads. Farmers were perceived the most economically affected stakeholder group with forgone income due to unsold pigs, costs for implementing biosecurity measures and extra costs for feeding unsold pigs being the major perceived causes of the losses. The continued trade in pigs and pig products in informal marketplaces suggests that quarantine might not be effective for hindering activities that might spread ASF in these settings. The perceived economic losses provide an insight into the negative economic impact of the quarantine for the different stakeholders.